2015
DOI: 10.4174/astr.2015.88.2.111
|View full text |Cite
|
Sign up to set email alerts
|

A rare nonincisional lateral abdominal wall hernia

Abstract: A 68-year-old woman presented a rare lateral abdominal wall hernia. Three month before admission to Chungbuk National University Hospital, she found a large protruding mass measuring 8 cm in diameter in the midaxillary line just below the costal margin upon heavy coughing. She had no history of abdominal trauma, infection, or operation previously. The mass was easily reduced manually or by position change to left lateral decubitus. CT scan showed a defect of the right transversus abdominis muscle and internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…4,5 In addition, long-term use of corticosteroids and cigarette smoking can weaken the abdominal wall. 2 Sundström and colleagues 3 conducted a study involving 1,072 HIV-infected patients. They showed that HIV-infected patients who used ART had a high incidence of abdominalwall hernias.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In addition, long-term use of corticosteroids and cigarette smoking can weaken the abdominal wall. 2 Sundström and colleagues 3 conducted a study involving 1,072 HIV-infected patients. They showed that HIV-infected patients who used ART had a high incidence of abdominalwall hernias.…”
Section: Discussionmentioning
confidence: 99%